2020
DOI: 10.3390/jmse8100811
|View full text |Cite
|
Sign up to set email alerts
|

Investment Analysis of Waste Heat Recovery System Installations on Ships’ Engines

Abstract: This study considers incentive provisions for investment decisions related to waste heat recovery system (WHRS) installations on ships to reduce CO2 emissions and improve ships’ engine efficiency. The economic assessment of WHRS installations in the shipping sector is not widely covered in the literature. A reason for this might be that the conventional financial evaluation of sensitive choices is commonly done through capital budgeting methods, which are not flexible enough to integrate future changes in fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Atari S. et al [36] introduced real option approaches for modeling the volatile frame condition for assessing green technologies investments. Olaniyi E. and Prause G. [37] used mathematical option models to evaluate the financial performance of energy-saving measures. The authors concluded that the financial result of such investments strongly depends on the economic environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Atari S. et al [36] introduced real option approaches for modeling the volatile frame condition for assessing green technologies investments. Olaniyi E. and Prause G. [37] used mathematical option models to evaluate the financial performance of energy-saving measures. The authors concluded that the financial result of such investments strongly depends on the economic environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, one must be aware that RE investments' economic performance still strongly depends on the reference price of fossil fuel, as E.O. Olaniyi and G. Prause [50] pointed out. The authors note that it is necessary to choose a diversified strategy of a country's energy development regarding state energy security without concentrating on any type of energy-either RE or fossil fuels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By considering the activities of the International Maritime Organization (IMO), an emphasis lays on limiting all kinds of emissions, to reduce energy consumption and to safeguard a clean maritime environment. Hence, new approaches for ships and ports are required to improve energy efficiency, reduce emissions and realise greener maritime operations [28]. An important instrument for hoisting sustainability gains in the maritime sector lies in digitalisation [9]- [12], whereby the improvement potentials heavily depend on the regional (digital) technological readiness and innovation potential [29], [30].…”
Section: Theoretical Backgroundmentioning
confidence: 99%